Negotiating truth, freedom and self : the prison narratives of some South African women - Young, Sandra Michele (Department of English Language and Literature, 2016)
The autobiographical prison writings of four South African women - Ruth First, Caesarina Kana Makhoere, Emma Mashinini and Maggie Resha - form the focus of this study. South African autobiography is burdened with the task of producing history in the light of the silences enforced by apartheid security legislation and the dominance of representations of white histories. Autobiography with its promise of 'truth' provides the structure within which to establish a credible subject position. In chapter one I discuss the use of authenticating devices, such as documentary-like prose, and the inclusion in numerous texts of the stories of others. Asserting oneself as a (publicly acknowledged) subject in writing is particularly difficult for women who historically have been denied access to authority: while Maggie Resha's explicit task is to highlight the role women have played in the struggle, her narrative must also be broadly representative, her authority communal. As I discuss in chapter two, prison writing breaks the legal and psychological silences imposed by a hostile penal system. In a context of political repression the notion of the truth becomes complicated, because while it is important to be believed, it is also important, as with Ruth First, not to betray her comrades and values. The writer must therefore negotiate with the (imagined) audience if her signature is to be accepted and her subjectivity affirmed. The struggle to represent oneself in the inimical environment of prison and the redemptive value in doing so are considered in chapter three. The institution of imprisonment as a means of silencing political dissidence targets the body, according to Michel Foucault's theories of discipline and control explored in chapter four. Using the work of Lois McNay and Elizabeth Grosz I argue in chapter five that it is necessary also to pay attention to the specificities of female bodies which are positioned and controlled in particular ways. I argue, too, using N. Chabani Manganyi, that while anatomical differences provide the rationale for racism and sexism, the body is also an instrument for resisting negative cultural significations. For instance, Caesarina Kana Makhoere represents her body as a weapon in her political battle, inside and outside prison. The prison cell itself is formative of subjectivity as it returns an image of criminality and powerlessness to the prisoner. Following the work of human geographers in chapter six I argue that space and subjectivity are mutually constitutive, as shown by the way spatial metaphors operate in prison texts. The subject can redesign hostile space in order to represent herself. As these texts show, relations of viewing are crucial to self-identification: surveillance disempowers the prisoner and produces her as a victim, but prisoners have recourse to alternative ways of (visually) interacting in order to position the dominators as objects of their gaze, through speaking and then also through writing. Elaine Scarry's insights into torture are extended in chapter seven to encompass psychological torture and sexual harassment: inflicting bodily humiliation, as well as pain, on the body, brings it sharply into focus, making speech impossible. By writing testimony and by generating other scenes of dialogue through which subjectivity can be constructed (through being looked at and looking, through having the message of self affirmed in the other's hearing) it is possible to contain, in some way, the horror of detention and to assert a measure of control in authoring oneself. For Mashinini this healing dialogue must take place within an emotionally and ideologically sympathetic context. v For those historical subjects who have found themselves without a legally valued identity and a platform from which to articulate the challenge of their experience, writing a personal narrative may offer an invaluable chance to assert a truth, to reclaim a self and a credibility and in that way to create a kind of freedom. Bibliography: pages 173-182.